The Effect of Physical Activity on Reducing Blood Sugar Levels in Type-2 Diabetes Mellitus Patients: Systematic Review - Geladis Titanik; Andri Setiya Wahyudi; Ika Nur Pratiwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to abnormal insulin secretion. Diabetes mellitus is characterized by increased blood sugar levels exceeding normal limits, due to a deficiency of the insulin hormone produced by the pancreas, causing a decrease in blood sugar levels. This study aims to determine the effect of physical activity on reducing blood glucose levels in patients with type 2 diabetes mellitus. Methods: Literature searches were conducted on the following databases: PubMed, Embes, Web of Science, and Scopus. By including all observational studies, randomized controlled trials, quasi-experiments, case controls, and pre-experiments and radiating their quality using the Joanna Briggs Institute tool often referred to as (JBI). Criteria: Articles in English, published in internationally recognized journals, and discussing physical activity in relation to lowering blood glucose levels. Results: Fifteen studies ranging in size from 28 to 100 participants physical activity is effective in lowering blood glucose levels with regular exercise three times a week physical exercise can be applied to the age range of 30-85 years. Conclusion: For people with type 2 diabetes mellitus, physical activity plays a very important role in controlling blood glucose levels. When exercising, blood sugar levels are much lower than when not exercising. It can be concluded that physical activity can lower blood sugar levels in people with type 2 diabetes.